TATHWIR AL LU’BAH “BRAIN’S ADVENTURE” LI TANMIYATI DZAKIROH QOSHIROTUL MADAY LADAY THULLAB FI TA’LIM ALAROBIYYAH - Qomariyah, Lailatul; Niswah Mz, Isniyatun; Qodir, Abdul; Mu’at, Mu’at; Ilahiyah, Iva Inyatul; Hakim, Luthfi; Kuswanti, Nur (El-Tsaqafah : Jurnal Jurusan PBA, 2024)
It turns out that the phenomenon in teaching Arabic is that students' thinking skills are still low. This phenomenon is evident in the number of students who give wrong answers to Arabic language questions that require deep thinking during Arabic language teaching. This is not consistent with the current curriculum that requires students to develop their mentality, specifically to think either critically or creatively. This phenomenon indicates that the level of thinking skills, especially in short-term memory, among students is still low. Therefore, the aim of this research is to develop the game "Brain Adventure" to develop short-term memory among students in teaching Arabic to sixth grade primary school students. The method used in this research is developmental research with the ADDIE development model. This model is implemented in several stages, namely analysis, design, development, implementation, and evaluation. The researchers focused on the first four stages. The results of this research are: the first stage of this research is the analysis of the curricula, the analysis of the materials, and the analysis of the students' memory abilities. The second stage is the design of questions and materials according to the curriculum. The third stage is the development of the game using the adventure model. The fourth stage is the implementation, which includes testing the material experts and educational media experts before implementing the developed game on small topics. As for the results of the questionnaire, the level of feasibility of the adventure game from the experts falls into the value "very good". This indicates that this game is suitable for use in teaching the Arabic language as a teaching tool to develop short-term memory in students.